2011
DOI: 10.1038/sc.2011.59
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor training using a robotic device in patients with subacute spinal cord injury

Abstract: Study design: Quasi experiment; single experimental group with matched historical control. Objectives: To evaluate the effect of an additive robotic-assisted gait training (RAGT) using the Lokomat system on the neurological and functional outcomes of patients with subacute spinal cord injury (SCI). Setting: Department of Physical Medicine and Rehabilitation. Methods: A total of 28 subacute SCI patients were treated by RAGT, 2-3 times a week, 30-45 min every treatment, concomitantly with regular physiotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…11 Regarding the SCIM score it is known that locomotor training leads to an increase in SCIM points, especially in the mobility section. 12 This was also shown in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…11 Regarding the SCIM score it is known that locomotor training leads to an increase in SCIM points, especially in the mobility section. 12 This was also shown in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…One such device is the LOKOMAT (Hocoma, Switzerland), a powered device that provides robotic-assisted step training (RAST) similar to BWSTT, but through a motorized exoskeleton that attaches to the patient’s legs, rather than manual positioning by a therapist (Colombo et al, 2000). Recent results have shown that RAST can improve walking capacity by improving gait speed, endurance, or temporal patterns of electromyographic (EMG) activity (Field-Fote et al, 2005, Hornby et al, 2005, Mazzoleni et al, 2011, Schwartz et al, 2011, Wirz et al, 2005). It has also been shown that RAST can improve spasticity as measured by the Pendulum Test (Manella et al, 2010) and reflex excitability (Manella and Field-Fote, 2013), but had no significant impact on hypertonia as measured by the Modified Ashworth Scale (MAS) (Manella and Field-Fote, 2013, Manella et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…After training, manual muscle test scores of wrist extensor, finger flexor and finger abductor are significantly increased [47] . Another study demonstrated that the robotic-assisted gait training using the locomat system improved the functional outcome of subacute SCI patients [48] .…”
Section: Chronic Rehabilitation Period Of Scimentioning
confidence: 99%